#
Please explain steps after the steps :

At equilibrium, Y = C + l

We know, C = $\overline{c}$ + bY

Substituting value of C, we get, Y = $\overline{c}$ + bY + l

Y - bY = $\overline{c}$ + l

Y(1 - b) = $\overline{c}$ + l

$Y=\frac{1}{\left(1-b\right)}\times \left(\overline{c}+l\right)\phantom{\rule{0ex}{0ex}}bisnothingbuttheMPC.So,wehave:\phantom{\rule{0ex}{0ex}}Y=\frac{1}{\left(1-MPC\right)}\times \left(\overline{c}+l\right)$

Due to maths processing error, your query could not be solved. We request you to post query clearly so that you can get accurate results from our Experts

Regards

**
**